THE ROLE OF COMPLIANCE AND GRATITUDE IN IMPROVING THE PSYCHOLOGICAL WELL-BEING OF EARLY CHILDHOOD EDUCATION TEACHERS: A LITERATURE REVIEW - Ningsih, Yuniati; Farid, Muhammad; Arifiana, Isrida Yul (Antis-Publisher, 2026)
Objective: This study aims to comprehensively review the role of obedience and gratitude in improving the psychological well-being of non-civil servant early childhood education (PAUD) teachers, particularly in Islamic boarding schools (pesantren). Early childhood education (PAUD) teachers face significant challenges related to financial well-being, employment status, and high workloads, which have the potential to cause stress and reduce psychological well-being. Method: Through a literature review, this study found that obedience based on self-awareness, religious values, and moral responsibility can provide a sense of security, order, and satisfaction in carrying out tasks. Results: Meanwhile, gratitude has been shown to play a significant role in fostering positive emotions, reducing stress, strengthening social relationships, and helping teachers interpret limitations as a form of devotion. In the context of Islamic boarding school culture, the value of obedience reflected in the philosophy of